2016
DOI: 10.1038/mt.2016.71
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: CRNDE Promotes Malignant Progression of Glioma by Attenuating miR-384/PIWIL4/STAT3 Axis

Abstract: Colorectal neoplasia differentially expressed (CRNDE) is the most upregulated long noncoding RNA (lncRNA) in glioma. Herein, the function and potential molecular mechanisms of CRNDE and miR-384 were illustrated in glioma cells. CRNDE overexpression facilitated cell proliferation, migration, and invasion, while inhibited glioma cells apoptosis. Quantitative real-time polymerase chain reaction (PCR) demonstrated that miR-384 was downregulated in human glioma tissues and glioma cell lines. Moreover, restoration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
164
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(169 citation statements)
references
References 60 publications
(72 reference statements)
4
164
0
Order By: Relevance
“…Determination of the mechanism of lncRNA in sepsis may be helpful to discover novel therapeutic targets. Colorectal neoplasia differentially expressed (CRNDE) is an lncRNA, differentially expressed in colorectal tumors, and its aberrant expression in multiple cancers has been validated in accumulating reports as well . It is worth noting that abnormally expressed CRNDE is linked to inflammatory response and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the mechanism of lncRNA in sepsis may be helpful to discover novel therapeutic targets. Colorectal neoplasia differentially expressed (CRNDE) is an lncRNA, differentially expressed in colorectal tumors, and its aberrant expression in multiple cancers has been validated in accumulating reports as well . It is worth noting that abnormally expressed CRNDE is linked to inflammatory response and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of CRNDE is highly elevated in colorectal adenomas and carcinomas. CRNDE is the gene symbol or colorectal neoplasia differentially expressed, a novel gene the expression of which is highly elevated in colorectal adenomas and carcinomas (data from UCSC Genome Browser) 10. Growing evidence has indicated that CRNDE acts through epigenetic mechanisms to regulate cell differentiation/pluripotency, which may relate to its deregulation in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CRNDE expression is significantly upregulated in many cancers, including colorectal cancer and gliomas. Elevation in CRNDE expression has been shown to promote cell proliferation, migration and invasion while inhibiting apoptosis of glioma cells 10. Collective evidence has indicated that CRNDE is associated with adverse clinical characteristics and poor prognosis by regulating miRNAs in many solid tumors 11,12.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma is the most lethal primary central nervous system tumour, leading to significant mortality worldwide annually . Ma et al reported that lncRNA‐ATB expression was significantly increased in glioma tissues and cell lines compared with that in normal brain tissues and was associated with poor outcomes in glioma patients.…”
Section: Lncrna‐atb Deregulation In Human Cancersmentioning
confidence: 99%